APLIKASI SISTEM PAKAR UNTUK MENENTUKAN EKSTRAKULIKULER TERHADAP MINAT BAKAT SISWA ( STUDI KASUS DI SMPN 5 KOTA JAMBI ): Application,Expert System, Determining, Extracurricular, Interests and Talents, Forward Chaining - Louis, Ahmad; Putri, Dwi (JURNAL AKADEMIKA, 2019)
Expert system application to determine extracurricular to interest and talent of student influence to student academic activity. With the software to determine the extracurricular students, it is expected that each student can focus more on the interests and talents. Decision to determine the extracurricular students made for the teacher Counseling Guidance (BK). The purpose of this thesis is to develop an application to determine extracurricular activities for students' interest in talent in the junior high school 5 of Jambi City. The expert system determines extracurricular on the interests and talents of junior high school students helping teachers in determining extracurricular activities suitable for their students based on students' interests and talents. This thesis uses the forward chaining method to diagnose student extracurricular which is right for students. Based on the test results, and this system was built using a programming language based on Visual Basic 6.0 and MySQL database. This expert system application is useful to help and facilitate the user in determining the right extracurricular in accordance with the interests, talents and abilities of students.